2021
DOI: 10.1097/mog.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cirrhotic cardiomyopathy

Abstract: Purpose of review Cirrhotic cardiomyopathy (CCM) is a well-recognized entity. When patients with CCM encounter challenges such as liver transplantation, overt cardiac dysfunction manifests, leading to morbidity and mortality. Although revised diagnostic criteria for CCM have recently been proposed, these still need to be validated. Recent findings Previous reviews have summarized the mechanisms of CCM, such as abnormalities of the β-adrenergic pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…This retrospective study enrolled patients aged 18-70 years, diagnosed with decompensated cirrhosis (8) at the Affiliated Hospital of Qingdao University, Qingdao, China, between January 2018 and March 2021. Patients were divided into two groups (DD or non-DD group), according to echocardiographic examinations of cardiac diastolic function a week before operation, based on the revised 2019 CCC criteria (9)(10)(11). DD was determined if three of the following criteria were met: E/e' > 15, LAVI > 34 ml/m 2 , e' < 7 cm/s or TRV > 2.8 m/s.…”
Section: Study Design and Participant Selectionmentioning
confidence: 99%
“…This retrospective study enrolled patients aged 18-70 years, diagnosed with decompensated cirrhosis (8) at the Affiliated Hospital of Qingdao University, Qingdao, China, between January 2018 and March 2021. Patients were divided into two groups (DD or non-DD group), according to echocardiographic examinations of cardiac diastolic function a week before operation, based on the revised 2019 CCC criteria (9)(10)(11). DD was determined if three of the following criteria were met: E/e' > 15, LAVI > 34 ml/m 2 , e' < 7 cm/s or TRV > 2.8 m/s.…”
Section: Study Design and Participant Selectionmentioning
confidence: 99%
“…Cardiac dysfunction in patients with cirrhosis includes both structural and functional cardiac abnormalities and these changes have been gathered as the entity: Cirrhotic cardiomyopathy (CCM). 1 Numerous studies have demonstrated the clinical importance of CCM as a contributing factor in the development of complications and risk of death in patients with cirrhosis. [2][3][4] Nevertheless, the underlying pathogenesis of these cardiac abnormalities is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…It comprises a triad of impaired myocardial contractile responses to stress (systolic dysfunction), inadequate ventricular relaxation (diastolic dysfunction), and electrophysiological abnormalities in the absence of any known cardiac disease ( 3 ). Patients with cirrhosis may have various cardiovascular complications and even induce heart failure under stress conditions such as load or clinical invasive operation ( 4 , 5 ). Heart failure due to CCM is claimed to the third cause of mortality in liver transplant patients following infection and rejection ( 6 ).…”
Section: Introductionmentioning
confidence: 99%